The Effect of Learning Organization and Self-Efficacy on the Performance of Small and Medium Industries in the Dried Culinary Field in Bojonegoro - Luvi Ekananda Widodo; Endang Iryanti (Indonesian Journal of Business Analytics, 2023)
The rapid growth in the number of Small and Medium Industries (IKM) cannot be avoided because the main role in determining the course of IKM is Human Resources (HR). Human resources are the main capital that determines the course of IKM because the success of a business is determined by the individuals involved in it. The purpose of this study was to determine the effect of learning organization and self-efficacy on the performance of small and medium-sized dry culinary industries in Bojonegoro. The sampling technique used was the saturated sampling technique, so the number of samples taken was 48 IKM actors in the dry culinary field at the Bojonegoro Creative Economy Center (CEC) Community. The research method used for this research is quantitative. The data analysis technique in this research uses Partial Least Square (PLS). According to the findings of the study, self-efficacy and learning organization have a significant positive impact on the performance of Bojonegoro's small and medium-sized industries in the dry culinary industry.